KARAKTERISTIK DAN KUALITAS BIOCHAR DARI PYROLYSIS BIOMASSA TANAMAN BIO-ENERGI WILLOW (SALIX SP) - C. Prayogo; N D. Lestari; K S. Wicaksono (Universitas Tribhuwana Tunggadewi, 2012)
Biochar now is importance issue due to complication same meaning with “charcoal”.In development country techonology convert biomass becomes energy is called “pyrolysis“ to produce several gas such as bio-oil and biochar. Biochar produce from crop ussually consist some importance nutrient, and called as “negative carbon emitter“. In this experiment characteristic and quality bichar is produce from Fluidized Bed Reactor to usefull biomass of bio energy willow (Salix sp) at diffferent temperature 450oC, 470oC and 530oC. Evaluation was made by using LECO-2000, ICP (Inductively Coupled Plasma), SEM (Scaing Electron Microscop) and FTIR (Fourier Tranfrmed Infrared).The research result showed that increased tempereture “pyrolysis“ from 440oC to 530oC signifantly affected end product chemical composition, porous content and functional point from biochar. Additing Potassium (K) and Phosphor (P) found higher content compare the original source. On the other hand, in high temperature, all functional organic source: phenol,amine,carboxylic ,aromatic and polysacharida did not detiction